Effect of Nanoscale Carbon Black, Ammonium Polyphosphate, and Microcrystalline Cellulose on Properties of Polypropylene Composites - İlkay Atar (BioResources)
The effects of nano-sized carbon black (CB), ammonium polyphosphate (APP), and microcrystalline cellulose (MCC) were tested relative to the mechanical and thermal properties of polypropylene (PP)-based composites. Composites were produced by injection molding in nine different combinations by adding materials at the levels of 0% or 10% MCC, 0% or 15% APP, and 0% to 7% CB. With the use of APP, there was a decrease in tensile and flexural strength, while there was an increase in impact resistance. Compared to the control group, it was determined that with the use of CB and MCC, there was an increase in tensile modulus, flexural strength, flexural modulus, and impact strength, while there was a decrease in tensile strength and elongation at break values. The flexural strength and flexural modulus values of all PP composites were higher than the standard values for polyolefin-based plastic lumber decking boards. A decrease in the initial degradation temperature occurred with the addition of MCC. As the CB usage was increased and MCC was added, the amount of charred residue increased. Additionally, the use of CB and the addition of MCC increased the maximum and final degradation temperatures compared to the control sample. Considering the results obtained, it was concluded that the use of CB and MCC generally improved the mechanical and thermal properties of PP composites.